FREQUENCY OF ROTA VIRUS AMONG CHILDREN < 5 YEARS WITH ACUTE DIARRHEA: A HOSPITAL BASED STUDY IN DUHOK / IRAQ - SALIM, ASHTI ASSIM M. (Fırat Üniveristesi, 2022)
Rotavirus, özellikle gelişmekte olan ülkelerde 5 yaş altı çocukların arasındaki ölüm ve hastalıkların sebebi olan ishalin en önemli etkenidir. Bu çalışmanın amacı 5 yaş altında olan ve barsak enfeksiyonu nedeniyle hastaneye başvuran çocuklarda rotavirüs' ün prevalansını Elisa testityle ölçmek ve Elisa testinin geçerliliğini PCR destekleyici test ile karşılaştırmasını yapmaktır. Hasta ve metot olarak Kesitsel bir çalışma modeli uygulanmışttır. İşlemler için etik komitesinin onayı alınmış ve hastalara işlemler etik kurallar çerçevesinde uygulannıştır. Çalışma, Duhok/ Irak'ta, ikinci basamak bir hastaneye başvuran her iki cinsiyette akut ishalden muzdarip 5 yaş altı 310 çocuğu kapsamaktadır. Dışkı örnekleri bu çocuklardan ocak – haziran ayları (2021) arasında toplanmış ve Rotavirüs antijeni için Elisa testinde Yürütülmüştür. Ayrıca, anne ve baba eğitimi, yaş, Cinsiyet, evlerdeki kalalablık indeksi, kentsel ve kırsal yerleşim, yaşamın ilk yılında beslenme uygulaması, rotavirus aşısı ve geçen ay ishal olma durumuna ait bilgiler toplanmıştır. Elisa testinin geçerliliği PCR ile daha fazla test edilen pozitif ve negative vakaların bir alt örneği alınarak ölçülmüştür. Rotavirüs'ün Elisa testi ile elde edilen prevalansi 29 % olarak saptanmıştır. Yaş, cinsiyet, kalabalık indexi ve rotavirus enfeksiyonu açısından anlamlı bir ilişki saptanmamıştır. Öte yandan rotavirus enfeksiyonu ile; okuma yazma bilmeyen veya daha düşük eğitime sahip olanlar arasında, eğitimli aile oranı daha yüksek ve yaşamın ilk yılında biberonla beslenme, kentsel yerleşme, kısmi veya tam aşılama rotavirüse karşı koruma sağlama arasında önemli bir ilişki olduğu bulunmuştur. Ayrıca Sonuçlar, hastaneye yatıştan önceki ayda daha fazla ishal nöbeti geçiren çocukların yalnızca bir ishal atağı geçirenlere göre rotavirus infeksiyonu prevalansinin önemli ölçüde daha düşük olduğunu ortaya koymuştur. Altın standart olarak PCR 'a kıyasla Elisa testinin geçerliliği, yine PCR ile test edilen 45 pozitif ve 65 negatif Elisa numünesi üzerinde de ölçülmüştür. Sonuçlar, bir pozitif ve bir negative testin duyarlılık, özgünlük , öngörücü değerlerinin, bir pozitif ve bir negatif olasılık oranlarının sırasıyla, %88.89, %100, %100, % 92.86, tanımlanmayan ve 0.113 olduğunu ve tanısal doğruluğunun Elisa testi % 95.45 olarak belirlenmiştir. Sonuçta, Rotavirus Duhok/ Irak' ta özellikle bebeklerde önemli bir barsak enfesksiyonu nedeni olduğu saptanmıştır. 5 yaşından küçük tüm çocukların geçerli bir test olan Elisa testi ile rotavirus taramasından geçirilmelidir. Ayrıca aşılama önemli bir önlem olup hastalıkların kontrolü için tavsiye edilmektedir.

Background: Rotavirus is the most important cause of diarrhea among children less than 5 years of age causing high morbidity and mortality, particularly in developing countries. Aims: The aims of the present work is to measure the prevalence of rotavirus diarrhea among children less than 5 years who visited a referral hospital suffering from acute gastroenteritis by ELISA test; and to measure the validity of ELISA test in comparison to PCR confirmatory test. Patients and Methods: Across sectional study design was adopted. Approval of the ethics committee was obtained and the procedures were carried out according to the ethical roles. The study included 310 children aged less than 5 years of both genders who diagnosed by specialist to be suffering from acute diarrhea; at a secondary care hospital in Duhok /Iraq . Stool samples were collected form those children during the period January–June, 2021, and then ELISA test was conducted for Rotavirus antigen. Information were also collected regarding: age, gender, father and mother education, crowding index in houses, urban/rural residency, feeding practice in the first year of life, vaccination to Rotavirus and attaches of diarrhea suffered in last month. The validity of ELISA test was measured by taking a sub sample of positive and negative cases who were further tested by PCR. Results: The prevalence of Rotavirus by ELISA test was found as 29%. No significant association was detected regarding age, gender, crowding index and Rotavirus infection. On the other hand there was a significant association between Rotavirus infection and; education family with higher rate among those with illiteracy or lower education and urban residency exclusive bottle feeding in the first year of life, while partial or complete vaccination gave protection to Rotavirus. The results also revealed that children who had more attacks of diarrheas in the month preceding admission had significantly lower prevalence of Rotavirus infection than those who had only one attack of diarrhea. The validity of ELISA test in comparison to PCR as gold standard was measured on 45 positive and 65 negative ELISA samples who were also tested by PCR. The results showed that the sensitivity, specificity, predictive values of a positive and a negative test, likelihood ratios of a positive and a negative were 88.89%, 100%, 100%, 92.86%, unidentified and 0.113 respectively, and the diagnostic accuracy of the ELISA test was determined as 95.45%. Conclusions: Rotavirus is an important cause of gastroenteritis, particularly among infants, in Duhok, Kurdistan Region, Iraq. All children less than 5 years who are admitted with gastroenteritis should be scanned for Rotavirus with ELISA test; which found to be a valid screening test. Also vaccination was an important measure and recommended for the control of the diseases. Background: Rotavirus is the most important cause of diarrhea among children less than 5 years of age causing high morbidity and mortality, particularly in developing countries. Aims: The aims of the present work is to measure the prevalence of rotavirus diarrhea among children less than 5 years who visited a referral hospital suffering from acute gastroenteritis by ELISA test; and to measure the validity of ELISA test in comparison to PCR confirmatory test. Patients and Methods: Across sectional study design was adopted. Approval of the ethics committee was obtained and the procedures were carried out according to the ethical roles. The study included 310 children aged less than 5 years of both genders who diagnosed by specialist to be suffering from acute diarrhea; at a secondary care hospital in Duhok, Kurdistan Region, Iraq. Stool samples were collected form those children during the period January–June, 2021, and then ELISA test was conducted for Rotavirus antigen. Information were also collected regarding: age, gender, father and mother education, crowding index in houses, urban/rural residency, feeding practice in the first year of life, vaccination to Rotavirus and attaches of diarrhea suffered in last month. The validity of ELISA test was measured by taking a sub sample of positive and negative cases who were further tested by PCR. Results: The prevalence of Rotavirus by ELISA test was found as 29%. No significant association was detected regarding age, gender, crowding index and Rotavirus infection. On the other hand there was a significant association between Rotavirus infection and; education family with higher rate among those with illiteracy or lower education and urban residency exclusive bottle feeding in the first year of life, while partial or complete vaccination gave protection to Rotavirus. The results also revealed that children who had more attacks of diarrheas in the month preceding admission had significantly lower prevalence of Rotavirus infection than those who had only one attack of diarrhea. The validity of ELISA test in comparison to PCR as gold standard was measured on 45 positive and 65 negative ELISA samples who were also tested by PCR. The results showed that the sensitivity, specificity, predictive values of a positive and a negative test, likelihood ratios of a positive and a negative were 88.89%, 100%, 100%, 92.86%, unidentified and 0.113 respectively, and the diagnostic accuracy of the ELISA test was determined as 95.45%. Conclusions: Rotavirus is an important cause of gastroenteritis, particularly among infants, in Duhok, Kurdistan Region, Iraq. All children less than 5 years who are admitted with gastroenteritis should be scanned for Rotavirus with ELISA test; which found to be a valid screening test. Also vaccination was an important measure and recommended for the control of the diseases.
5 yaş altı çocuklarda rotavirüs ün akut ishal ile yaygınlığı, Irak/ Duhok'da hastahane bazlı bir çalışma
Keywords: Biyoloji